Television journalism, crime news and sourcing practices : Findings from Argentina - Calzado, Mercedes (Matrizes.)
This paper presents the results of a research project on the new modes of production of television crime news. The enquiry involved monitoring television newscasts of the five major channels in Buenos Aires City and interviews with news workers. We analyze the news content, the ways of narrating and enunciating crime news on television, the role played by the police in the structure of the news, the emergence of new sources of information and the production routines of crime news. Our findings suggest that most of the newscasts on television give prominence to crime news within their agendas and that its production and presentation has changed as the result of the spread of digital technologies as sources of information.